2008
DOI: 10.2174/138955708785740580
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids: Cellular and Molecular Mechanism of Action in Glucose Homeostasis

Abstract: The purpose of this review is to discuss the cellular and molecular mechanisms of action of flavonoids focusing on carbohydrate metabolism. The beneficial effects of flavonoids have been studied in relation to diabetes mellitus, either through their capacity to avoid glucose absorption or to improve glucose tolerance. Furthermore, flavonoids stimulate glucose uptake in peripheral tissues, regulate the activity and/or expression of the rate-limiting enzymes in the carbohydrate metabolism pathway and act per se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 0 publications
3
54
0
6
Order By: Relevance
“…The impairment in the regulation of blood glucose level may lead to an imbalance that may lead to hyperglycemia thus Type 2 diabetes necessitating proper management [41]. Polyphenols are plant chemicals that possess hypoglycemic potentials [45]. One mechanism through which this group of chemical modulate glucose metabolism is to stimulate the muscle and fat cells to increase their glucose utilization activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impairment in the regulation of blood glucose level may lead to an imbalance that may lead to hyperglycemia thus Type 2 diabetes necessitating proper management [41]. Polyphenols are plant chemicals that possess hypoglycemic potentials [45]. One mechanism through which this group of chemical modulate glucose metabolism is to stimulate the muscle and fat cells to increase their glucose utilization activities.…”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism by which the selected plants' extracts enhanced glucose utilization activities of the cells was not investigated, the limiting step of insulin stimulated the glucose uptake of muscle and fat is the translocation of GLUT4 transporters to the plasma membrane [49]. Studies showed that polyphenols are able to enhance the glucose utilization activity by either acting as insulin mimetic [50,51] or without affecting the insulin receptor autophosphorylation and/or transporter translocation to the plasma membrane [45]. One of these mechanisms might have been the action mode by which the plants' extracts enhanced the glucose utilization activities of the cells.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study has shown the presence of alkaloid, flavonoids, saponins and other chemical compounds in the plant extract [24]. Several of these constituents are well known for their antidiabetic activity [25,26]. This suggests that the antidiabetic activity of the extract may be partly due to the action of these phytoconstituents which could act synergistically or independently in reducing the blood glucose level.…”
Section: Discussionmentioning
confidence: 95%
“…Flavonoids have been shown to possess remarkable hypoglycaemic effects which have been linked to their capacity to avoid glucose absorption or improve glucose tolerance [74]. It has been demonstrated that flavonoids act as insulin secretagogues or insulin mimetics, attenuate diabetic complications, stimulate glucose uptake in peripheral tissues and regulate the activity and/or expression of the rate limiting enzymes involved in carbohydrate metabolism [75]- [77].…”
Section: Discussionmentioning
confidence: 99%